Separate and Combined Effects of Geometrical and Mechanical Properties Changes Due to Aging on the Femoral Strength in Men and Women - Sahandifar, Pooya; Kleiven, Svein (Frontiers in Mechanical Engineering, 2021)
Aging, from 40 to +80 years old, causes geometrical and mechanical properties changes in the proximal femur. The subperiosteal width expands faster in men compared to women during aging, while the cortical thickness varies unequally in each sector and differently between men and women. Another change which occurs during aging is bone mechanical properties such as stiffness and ultimate strains. Numerical analysis allows us to study the potential effects of each of the age-dependent changes on the fracture forces separately and combined. We investigated the effects of the geometrical and bone mechanical properties changes due to aging on the femoral strength during a common falling scenario using a transverse isotropic continuum damage model. First, the femur model was adapted from a previously developed human body model named THUMS v4.02. Then, three sets of models were developed to address each of the changes separately and combined for both sexes. We found that the fracture forces in women are on average 1500 N less than in men of the same age. The age-dependent geometrical changes increased the fracture forces in men (25 N/decade), whereas it reduced the fracture forces by 116 N/decade in women. The mechanical properties changes reduced the fracture forces in men more than in women (354.5 N/ decade vs. 225.4 N/decade). When accounting for both geometrical and mechanical properties changes due to aging, the fracture forces decreased by 10.7 percent of the baseline in women per decade compared to 7.2 percent per decade in men.